Peran Keluarga Perhadap Perilaku Gizi Anak Usia Sekolah - Andi Saifah; Junaiti Sahar; Widyatuti Widyatuti (Jurnal Keperawatan, 2019)
Nutrition problem is one of the health problems of school-age children which can cause physical, psychological and academic performance to decline. The purpose of this research is to analyze the relationship between the role of the family and the nutritional behavior of school-age children in the working area of ​​the Mabelopura Public Health Center in Palu. The research design was a cross sectional correlation study. The research population was 4944 students of elementary school. The number of samples was 174 students through cluster proportional sampling. Inclusion criteria, namely class of 4,5 and 6, are willing to be respondents and can read and write. The sample selection was done by drawing proportionally with attendance numbers. The research instrument was a weight scale, meter, questionnaire to measure the role of family and nutritional behavior with the validity test r-value between 0.361-0.718 and Cronbach α value> 0.9. Hypothesis testing using the Spearman correlation test, obtained p = 0.035, r = 0.16. The research concludes that there is a positive correlation between the role of family and nutritional behavior of school-age children, it is very important as an example of a good role and the provision in fulfilling balanced nutrition.